The Capability Threshold: Re-examining the Definition of the Middle Class in an Unequal Developing Country - Ronelle Burger; Camren McAravey; Servaas van der Berg (Institute for the Study of Labor (IZA), 2015)
In a polarised and highly unequal country such as South Africa, it is unlikely that a definition of the middle class that is based on an income threshold will adequately capture the political and social meanings of being middle class. We therefore propose a multi-dimensional definition, rooted in the ideas of empowerment and capability, and find that the 'empowered middle class' has expanded significantly since 1993 also across vulnerable subgroups such as blacks, female-headed households and rural inhabitants. It also is much larger than when measured in terms of income. Differing trends between the middle class defined based on income and based on capabilities is attributed to improved capabilities have not been rewarded with a proportional increases in access to the labour market. It is disconcerting that links to the labour market improved only slightly and this is attributed to sluggish labour market growth and low quality of education. We find that the middle class tend to have lower expectations around social mobility than the vulnerable. It is concerning that vulnerable individuals harbour unrealistically high expectations of the social mobility of the households and do not understand the determinants of social mobility and labour market prospects –possibly due to a mixture of heightened expectations following the political transition, but also the continued disconnection and marginalisation of vulnerable subpopulations from the mainstream economy.
Keywords: I32; I38; N97; D31; 330; middle class; capability approach; measurement; development; South Africa